1-ACETYLHYDROQUINONE 4-GALACTOSIDE FROM FERULAGO-AUCHERI - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1991)
From the chloroform extracts of the aerial parts of Ferulago aucheri two coumarins osthenol, prantschimgin (marmesin senecioate), two flavonoids isorhamnetin 3-galactoside, 6-hydroxyapigenin 6-methyl ether and two new aromatic compounds 1-acetylhydroquinone 4-galactoside and quinol monoacetate were isolated. The structures were established by spectral and chemical methods.
Keywords: FERULAGO-AUCHERI; UMBELLIFERAE; COUMARINS; FLAVONOIDS; AROMATIC COMPOUNDS; 1-ACETYLHYDROQUINONE 4-GALACTOSIDE